2019
DOI: 10.1007/s10865-018-00007-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk and management of physical diseases

Abstract: During the 40 years since the Yale conference on Behavioral Medicine and the founding of the Journal of Behavioral Medicine considerable progress has been made in understanding the role of psychosocial risk and management of physical diseases. We here describe the development of these fundamental concepts from early research on stress through studies of the Type A behavior pattern to more contemporary approaches to the relationship between psychosocial risks and benefits in relation to disease processes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 181 publications
(239 reference statements)
0
7
0
Order By: Relevance
“…Examples from the present study include how, compared to episodes among those who were housed, we found the group of episodes among PEH had significantly higher rates of unemployment, no income, receipt of public assistance, lacking health insurance, and arrests in the 30 days prior to admission and discharge. While the impact of SDOH on morbidity and mortality for many medical conditions [49][50][51] has been well documented, the literature on the impact of SDOH on MOUD outcomes or interventions is limited. [52][53][54] One existing study examining SDOH including income inequality and structural racism demonstrated an association with increased rates of injection drug use and worsened related outcomes such as HIV infection and AIDS-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Examples from the present study include how, compared to episodes among those who were housed, we found the group of episodes among PEH had significantly higher rates of unemployment, no income, receipt of public assistance, lacking health insurance, and arrests in the 30 days prior to admission and discharge. While the impact of SDOH on morbidity and mortality for many medical conditions [49][50][51] has been well documented, the literature on the impact of SDOH on MOUD outcomes or interventions is limited. [52][53][54] One existing study examining SDOH including income inequality and structural racism demonstrated an association with increased rates of injection drug use and worsened related outcomes such as HIV infection and AIDS-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that patients and families receive the psychological and social support that they require so they are able to mitigate barriers to care and maximize the benefits of care. This is especially important given increasing evidence on the benefits of psychosocial support for improving both the quality as well as the length of life of patients receiving cancer care. Our validated touchscreen‐based biopsychosocial screening tool could offer such support to help enhance clinical care of newly diagnosed cancer patients and patients on active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IBMs have been used to analyze different roles in regard to the vaccination, such as students, nurses, patients (Rosental & Shmueli, 2021;Wicaksana et al, 2023). Psychological variables can operate as independent promotive or risk factors for healthrelated behaviors (National Research Council (US) and Institute of Medicine (US) Board on Children et al, 2001;Schneiderman et al, 2019;Thomas et al, 2020), such as directly influencing (positively or negatively) vaccination intention. Promotional factors are personal psychological aspects, regardless they are vaccine-related or not, that directly influence the intention to get vaccinated by promoting it, whereas risk psychological factors are those that decrease that intention.…”
Section: Introductionmentioning
confidence: 99%